Gestión por procesos y su relación con la gestión por resultados en la registro nacional de identificación y estado civil Iquitos 2023 - Diaz Iglesias, Lizeth (2025)
The purpose of this research was to determine the relationship between management by processes and management by results in the National Registry of Identification and Civil Status, Iquitos, 2023. Opting for a basic study, quantitative approach and non-experimental cross-sectional design, the sample consisted of 15 employees for the survey conducted by two questionnaires for data collection. The findings show that 53% consider process management to be good, 27% perceive it as fair, while 20% rate it as bad; 66% rate it as good, while 20% rate it as fair and only 14% as bad. Therefore, it is determined that there is a high positive correlation between the variables by a coefficient of rho=0.809 and a significance p=0.000 (<0.05); indicating that there is a significant relationship between the variables. Likewise, the strategic processes dimension shows a coefficient and significance of rho=0.759 and p=0.000; similarly, the operational processes dimension shows a coefficient and significance of rho=0.741 and p=0.000; finally, the support processes dimension shows a coefficient and significance of rho=0.469 and p=0.000, these dimensions are significantly and positively related to management by results.